Need Need Analysis for the Design of an Online Module Based on Cognitive Conflict and the Deep Learning Approach to Correct Students’ Misconceptions About Light Waves - Kesya Yumna Salsabila; Fatni Mufit; Ratnawulan; Fauziah Ulmi (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2026)
Students’ conceptual understanding of light waves remains relatively low, while the instructional materials currently in use have not been able to optimally facilitate the remediation of misconceptions. This study aims to analyze the need to develop a cognitive conflict-based e-module integrated with the deep learning approach—an approach that emphasizes meaningful, reflective, and enjoyable conceptual understanding through the components of meaningful learning, mindful learning, and joyful learning. The integration of cognitive conflict with the deep learning approach in the topic of light waves represents a novelty in this research, given that previous studies generally focused only on one of these approaches or combined cognitive conflict with Augmented Reality technology. This study is a preliminary investigation within Plomp’s preliminary research model for instructional design, with data collected through interviews with 2 physics teachers and 3 students, as well as a four-tier multiple-choice diagnostic test administered to 31 twelfth-grade students in Phase F at MAN 3 in Padang. The analysis results indicate that 69.7% of students held misconceptions, while the instructional materials used were still dominated by printed textbooks and worksheets and did not support concept visualization or the remediation of misconceptions. These findings underscore the need to develop e-modules based on cognitive conflict and a deep learning approach that align with the needs of teachers and students, while also contributing to the development of digital physics instructional materials capable of visualizing abstract concepts and supporting the remediation of misconceptions more effectively.